Taking initiative in small-sided soccer games - Frencken, W.; Otten, E.; van der Plaats, J.; Visscher, C.; Lemmink, K. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
In many sports, players interact during a game. Dynamical systems theory provides tools to investigate these interactions by assessing phase relations. It has been suggested that a squash player with a lead phase relation has an advantage over the player with the lag phase relation with respect to rally outcome (McGarry et al., 2002). Therefore, phase delay between players might be a tool to investigate dominance during rally`s in racket sports (Palut & Zanone, 2005). It can be hypothesized that in ball team sports like soccer, a lead phase relation of the attacker increases the chance to score. Therefore, the aim was to investigate initiative in attacker-defender dyads in small-sided soccer games Methods Ten young male elite soccer players (17.3 years ± 0.7) participated in three small-sided soccer games (4-a-side plus goalkeepers) of 8 minutes on a 28x36m pitch. Player positions were recorded at 45Hz per player by means of innovative technology, i.e. local position measurement (LPM) system. Cross-correlations and delays were calculated for acceleration profiles of all players 25Hz over a sliding 2,5s interval (NBody software, UMCG Groningen). To exclude less relevant couplings between players, a cross-correlation coefficient of 0.4 was set as threshold value. Only couplings between the attacker and defender prior to a goal or goal-scoring opportunity were included in the analysis. The attacker was the player that attempted to score, whereas the defender was the opponent of that particular attacker. All couplings were investigated through visual inspection. Results In total, 66 goal-scoring opportunities were notated of which 19 resulted in a goal. Preliminary results show that for 65% of the goals and goals-scoring opportunities the attacker holds initiative, with no difference between goals and goals-scoring opportunities. In addition, we found that the percentage of the attacker`s initiative decreases with type of attack (100%, 85%, 55% and 33% for 1v1 situations, regular attacks, counter attacks and long distance shots respectively). Discussion Results indicate that attackers most frequently take initiative prior to goal-scoring opportunities. The absence of clear differences between goals and goal-scoring opportunities indicates that whether or not a goal is scored eventually, depends on other factors, e.g. technical ability, goalkeepers ability and luck. The trend we found for the attacker`s initiative for the different types of attack is in line with the task of the attacker in the various types of attack. In 1v1 situations, the attacker has to take initiative, whereas that is less required in long distance shots. Based on this study, it can be concluded that encouraging attackers to take initiative increases the chance to score and therefore to win the game.